Analisis Nilai-Nilai Budaya Cerita Rakyat “Cimangeunteung” dan Recana Pelaksanaan Pembelajarannya untuk Siswa SMA Tahun 2021 - Trikawati, Trikawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
The problems formulated in this study are: (1) are there cultural values in Cimangeunteung folklore?; (2) what cultural values are contained in Cimangeunteung folklore, Cimangeunteung Village, Rangkasbitung District?; and (3) what is the appropriate learning model for high school students? This purpose of the study is to obtain: (1) an overview of cultural values in Cimangeunteung folklore ; (2) the description of what cultural values are contained in Cimangeunteung folklore; and (3) an overview of the appropriate learning model for high school students in the Academic Year of 2021/2022. In this study, the descriptive method was used. It is a method that focuses on solving problems by collecting data, compiling, classifying, analyzing and interpreting and in the end, it would be described into descriptions of several sentences or paragraphs. The techniques used were observation, interviews, documentations and literature study. The results of the analysis regarding cultural values in Cimangeunteung folklore included words which, when classified, were divided into four parts, namely customs, life values and environmental management systems. These customs were usually agreed by the local community. Meanwhile, one of the life values was affection. When someone loves someone else, it means that he has feelings of affection for other people. Affection is the basis of life, family formation, close relationships in society and close human relationships.